The effect of service quality on customer loyalty; role of customer satisfaction as a mediation variable at Hananiah Tanah Abang store - Januarita, Handryani; Septiani, Iga; Erlina, Lita (Journal of Islamic Economics Management and Business (JIEMB), 2021)
Purpose – This study aims to measure the effect of service quality on customer loyalty at the Hananiah Tanah Abang store.Method – The sample of this research is 47 respondents at Hananiah shop. Statistical tests were performed using PLS-based Structural Equation Modelling. The validity test uses the loading factor value, while the reliability test uses Cronbach's alpha value, composite reliability and Average Variance Extracted (AVE).Result – (1.) The effect of service quality on employees at the Hananiah Tanah Abang store has a significant effect on customer satisfaction. (2.) The effect of customer satisfaction has a significant effect on customer loyalty. (3.) Customer satisfaction mediates the effect of service quality at Hananiah stores on customer loyalty.Implication – This study can assist businesses to improve their service quality.Originality – This is the first study examining the influence of service quality on customer loyalty with customer satisfaction as a mediation variable.